Entering a new era: The lived experiences of primary school teachers in the post-modular distance learning delivery - Rivera, Vicent Mae B.; Tabangan, Althea Maris P.; Tayanes, Patricia Isabelle M.; Comidoy, Ric Glenn A. (Universitas Airlangga, 2025)
This study explored the experiences of primary school teachers in the post-Modular Distance Learning (post-MDL) delivery, utilizing qualitative phenomenological design. In-depth interviews provided firsthand lived experiences of 8 primary school teachers from Peñaplata Central Elementary School SPED Center, Island Garden City of Samal, Davao del Norte, Philippines. Using QDA Miner Lite and inductive content analysis, the positive experiences of primary school teachers in the post-MDL delivery are consistent assessment and monitoring, social interaction, and macro-skills development and improvement. Parents' factors on learners' learning development, large class size, and pupils' attitudes and behavioral aspects are the themes for the negative experiences. The learning gap, lack of school resources and financial support, implementation of the Covid-19 safety protocols, and overlapping of teachers' workloads are the challenges for the teachers. Differentiated teaching techniques, implementation of classroom management and use of teachers' past experiences, teachers' flexibility, and specialized teacher's training are the themes for the coping mechanisms of teachers. Finally, the insights of teachers are their role and perseverance in the post-MDL, the importance of resources and a positive classroom environment, and preference for new normal face-to-face classes. The results have implications for the teaching and learning process in the post-Modular Distance Learning delivery.